Design of a Website-Based Employee Attendance Information System at PT. TOP AIRCONDITIONER - Destie Lia Syifa; Tia Yuniar; Malik Fajar; Sukanto Sukanto; Galuh Ardianti (Journal Collabits, 2025)
PT. Top Airconditioner is one of the companies engaged in AC service and air conditioning providers located at Permata Tangerang Blok DA No.11. PT. Top Airconditioner is currently using an outdated employee attendance system that involves collecting attendance data on paper, which is prone to loss and damage. This leads to delays in data recapitulation and ineffective management. To address this issue, a research was conducted to develop a web-based employee attendance system. The research utilized RAD analysis research method, UML system design, and PHP programming language with MySQL database. The main objectives were to create a system that allows employees to easily record their attendance daily and enables HRD to monitor attendance of employee more efficiently. The result of the research is a web-based employee attendance system that simplifies the process of recording attendance and enhances overall management. This new system will streamline the attendance process for PT. Top Airconditioner and improve HRD's ability to monitor attendance accurately.